HOLISTIC APPROACHES TO SMALL INTESTINAL BACTERIAL OVERGROWTH (SIBO): A REVIEW OF DIAGNOSTIC TOOLS AND COMBINED THERAPEUTIC STRATEGIES - Maciej Karwat; Oliwia Malec; Tytus Tyralik; Natalia Glanc; Dominik Sendecki; Izabella Michalska; Grzegorz Zalewski; Mateusz Myśliwiec; Julia Kular; Justyna Niebylecka (International Journal of Innovative Technologies in Social Science, 2025)
Background: Small Intestinal Bacterial Overgrowth (SIBO) is a complex gastrointestinal condition defined by excessive bacterial proliferation in the small intestine, often involving colonic species. Its prevalence is increasing, especially among individuals with irritable bowel syndrome, diabetes, or gastrointestinal motility disorders. SIBO presents with non-specific symptoms such as bloating, discomfort, and nutrient malabsorption, making diagnosis and treatment particularly challenging. Methods: This review is based on a narrative synthesis of peer-reviewed literature from 2007 to 2025, retrieved through PubMed and Google Scholar. Inclusion criteria focused on diagnostic tools and integrative treatment strategies for SIBO, including antibiotics, diet, phytotherapy, and gut–brain axis modulation. Only high-quality studies were selected. Results: SIBO is a multifactorial condition driven by motility disturbances, stress, dysbiosis, and anatomical abnormalities. While breath tests remain the most accessible diagnostic tools, their sensitivity is limited. Antibiotics such as rifaximin, metronidazole, and neomycin remain first-line therapy, yet symptom recurrence is common. Increasing attention is given to holistic management, including personalized low-FODMAP diets, herbal antimicrobials, digestive support, and gut–brain axis interventions. Patient-specific approaches, especially those addressing stress, sleep, and microbiota restoration, offer promising outcomes. However, implementation is challenged by inconsistent guidelines, insufficient follow-up, and varying patient adherence. Conclusion: Effective SIBO management requires early diagnosis and multifaceted treatment strategies that extend beyond temporary microbial suppression. Personalized care integrating diet, microbiota modulation, psychological support, and long-term monitoring may improve outcomes and reduce recurrence. Further research is needed to validate holistic protocols and refine diagnostic criteria.